Search for D-0-(D)over-bar(0) mixing and branching-ratio measurement in the decay D-0 -> K+pi(-)pi(0) - Aubert, B; Barate, R; Bona, M; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; et al. (2006)
We analyze 230.4fb-1 of data collected with the BABAR detector at the PEP-II e+e- collider at SLAC to search for evidence of D0-D̄0 mixing using regions of phase space in the decay D0→K+π-π0. We measure the time-integrated mixing rate RM=(0.023-0.014+0.018(stat.)±0.004(syst.))%, and RM<0.054% at the 95% confidence level, assuming CP invariance. The data are consistent with no mixing at the 4.5% confidence level. We also measure the branching ratio for D0→K+π-π0 relative to D0→K-π+π0 to be (0.214±0.008(stat.)±0.008(syst.))%. © 2006 The American Physical Society.